Método experimental/teórico para interpretação de semicondutores inorgânicos - Gouveia, Amanda Fernandes (Universidade Federal de São Carlos, 2018)
It is known that the morphology, dimensionality and crystalline structure of materials play important roles in electronic, optical, catalytic properties, among others. Understanding the role of these surfaces and find a relationship with their physical and chemical are of extreme importance. The theoretical calculations of the surfaces provide a deep knowledge about the kind of superficial defect, i.e. oxygen vacancies and local distortions, and how they are linked with the semiconductor properties, such as decrease of the band gap value, improve in the photocatalysis among others. One of the objectives of this project was to associate experimental and theoretical results in order to provide a better understanding of the structural and electronic properties of both zinc tungstate (ZnWO4) nanocrystals and silver tungstate (α-Ag2WO4) crystals, as representative inorganic semiconductors. By means of the first-principle calculations, based on the Wulff construction, it was possible to predict the morphology of these materials and, in particular, explaining how the photocatalytic process of the ZnWO4 nanocrystals occurs, as well as the effect of the surfactant on the photocatalytic activity of the as-synthetized α-Ag2WO4.
Experimental/theoretical method for interpreting inorganic semiconductors
Keywords: Semicondutor Inorgânico; Síntese; Morfologia; DFT; Construção de Wulff; Inorganic semiconductor; Synthesis; Morphology; Wulff construction; CIENCIAS EXATAS E DA TERRA::QUIMICA